Analysis of Human, Organizational, And Technological (Hot-Fit) Readiness in Medical Record Digitalization to Support The Implementation of Electronic Medical Record (EMR) at Bhayangkara Hospital Level IV Cianjur - Ridwan Yudiansyah; Vip Paramarta; Rulia Rulia (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the readiness of human, organizational, and technological aspects (HOT-Fit) in the digitalization of medical records to support the implementation of the Electronic Medical Record (EMR) at Bhayangkara Hospital Level IV Cianjur. The research background is based on the Indonesian Ministry of Health Regulation No. 24 of 2022, which mandates healthcare facilities to transition to electronic medical records, as well as the challenges faced by hospitals in terms of technological infrastructure, human resource skills, and system integration. This research employed a qualitative approach using in-depth interviews with medical staff, medical record officers, IT teams, and hospital management. Data were analyzed with NVivo software using the HOT-Fit model as the analytical framework. The results indicate that technology is the most dominant factor in the successful implementation of EMR, particularly regarding user-friendliness, system speed, and cross-service integration. Organizational aspects highlight the importance of structural support, policies, and clear SOPs, while human aspects focus on user competence and acceptance. EMR implementation has proven to deliver tangible benefits, including improved work efficiency, streamlined administrative processes, and enhanced healthcare quality. In conclusion, the success of EMR implementation is not solely determined by technological readiness but also by the synergy of human and organizational factors.